BAKTERI BERBENTUK BATANG PADA PEKASAM DURIAN (Duri zibhetinus L.) - Hasanuddin Hasanuddin (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2016)
Fermented durian is the fermented food prepared from spontaneous fermentation of durian (Durio zibethinus L) with or without salt by wild bacteria. Fermented durian is found not only in Indonesia as long as Sumatera island with the different names, but also in Malaysia. The sources data in this study was laboratory analysis. Productions center of fermented durian, traditional markets were sampled for the experiment. Sampels were collected every week in a month. Samples were analyzed microbiologically to determine and identify bacteria in fermented durian. There were two species of bacillus bacteria involved in fermented durian namely Lactobacillus plantarum and Lactobacillus curvatus. The specieses were included in lactic acid bacteria.Lactic acid (C2H5COOH) is the organic acid that can serve as a food preservation. The group of bacteria which can produce lactic acid in their fermentation process known as Lactic Acid Bacteria (LAB). A fundamental biochemical change of fermentation is that an acidic environment is created. Many harmful organisms cannot exist in acidic solution so the fermentation productions are save to eat.